New Trends and Design of User Centric Services in the Mahatma Gandhi University Library: A Study - Rajan M, Maghesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
University Libraries play vital role in education, learning, teaching and research, and acting as centre of learning in the higher education sector. University libraries have been acting as per the directions of the University Grants Commission and the parent university authorities subject to the basic norms of the concerned universities. User centric systems and services are basically meant for providing quality of services to its users and to empowerment of their leaning capacity. The services offered by the libraries differ from one another and based on the nature of the university and its discipline they depend. This paper attempts to bring out the new trends and changes introduced in the M G University by adopting new techniques and technologies in delivering user centric library services in changing digital era. This paper also attempts to study and evaluate the procedure of design of user centric services .